First record of Cabestana cutacea (Linnaeus, 1767) (Gastropoda; Ranellidae) found on the coast of Montenegro: notes about the range of the species - Doneddu, Mauro; Trainito, Egidio; Mačić, Vesna (Biologia Serbica, 2014)
We report the finding of two empty shells of the Ranellidae species Cabestana cutacea (Linnaeus, 1767) on the coast of Čanj, Montenegro. Although we cannot exclude that this may be the result of inadvertent human transport, these findings are of interest because this species has not been recently reported in the Adriatic Sea.